Cardiovascular Toxicity Related to Cancer Treatment: A Pragmatic Approach to the American and European Cardio‐Oncology Guidelines - Alexandre, Joachim (J Am Heart Assoc, 2020)
The considerable progress made in the field of cancer treatment has led to a dramatic improvement in the prognosis of patients with cancer. However, toxicities resulting from these treatments represent a cost that can be harmful to short‐ and long‐term outcomes. Adverse events affecting the cardiovascular system are one of the greatest challenges in the overall management of patients with cancer, as they can compromise the success of the optimal treatment against the tumor. Such adverse events are associated not only with older chemotherapy drugs such as anthracyclines but also with many targeted therapies and immunotherapies. Recognizing this concern, several American and European governing societies in oncology and cardiology have published guidelines on the cardiovascular monitoring of patients receiving potentially cardiotoxic cancer therapies, as well as on the management of cardiovascular toxicities. However, the low level of evidence supporting these guidelines has led to numerous discrepancies, leaving clinicians without a consensus strategy to apply. A cardio‐oncology expert panel from the French Working Group of Cardio‐Oncology has undertaken an ambitious effort to analyze and harmonize the most recent American and European guidelines to propose roadmaps and decision algorithms that would be easy for clinicians to use in their daily practice. In this statement, the experts addressed the cardiovascular monitoring strategies for the cancer drugs associated with the highest risk of cardiovascular toxicities, as well as the management of such toxicities.